DIRECT MARKETING OPPORTUNITIES THROUGH AGRICULTURE MARKET REFORMS (International Journal of Food and Nutritional Sciences, 2022)
The nature of the agricultural products is perishable in nature which is a big challenge for agricultural marketing. The rural primary markets and wholesale markets have lot of defects. To overcome the defects faced in agricultural marketing, direct marketing has a scope with several initiatives. Direct marketing eliminates middleman which benefits the farmers more. The available reforms in agricultural marketing are farm gate, factory premises, warehouses, silos and cold storages. With these reforms available there are lot of opportunities in direct marketing. This paper reveals the various opportunities available in direct marketing through agricultural market reforms.